University social responsibility in Latin America: Systematic review: Responsabilidad social universitaria en Latinoamérica: Revisión sistemática - Cuba Sancho, Juana Matilde (2023)
Introduction: University social responsibility is present in the discourses of academics, but it fails to permeate the actions that lead to the transformation of the university, requiring a paradigm shift. At present there are conceptual confusions that make its promotion and transformative practice very difficult, in many universities it is confused with social projection, which reduces its transversal dimension. Objective: To analyze the scientific evidence related to university social responsibility in Latin America. Methods: Systematic review of the literature, between the months of August to December 2021; the search for articles was carried out in the databases: Scopus, Scielo, Doaj, Lilacs and Redalyc; the use of Descriptors in Health Sciences (DeCS) and the combination of the Boolean operators OR and AND were applied. Full texts in Spanish between the years 2015 and 2021 were considered. Results: 508 articles were obtained, which were submitted to the PRISMA methodology, selecting 20 articles, grouped into four categories according to the Social Responsibility Manual of the Úrsula Model: management, training, cognitive, and social participation. Conclusions: USR is an inalienable moral commitment, it is important in university management to promote sustainable development, with ethics and respect for human rights, the participation of committed actors is necessary, considering that it currently has a welfare and reductionist approach, scarce support, socialization and implementation and there is a need to unify criteria.